Peran Orang Muda Katolik dalam Pewartaan Injil di Era Digital: Perspektif Teologi Pastoral tentang Pengudusan Dunia Digital - Margaretha Maria Wasti; Carolus Borromeus Mulyatno (Media: Jurnal Filsafat dan Teologi, 2026)
ABSTRAK (Indonesia): This study examines the role of Catholic Youth (Orang Muda Katolik/OMK) in proclaiming the Gospel in the digital era through a pastoral theological perspective on the sanctification of the digital world. Employing a qualitative phenomenological descriptive approach, data were collected through open-ended written interviews conducted online with 13 participants and supported by systematic literature review. The analysis was carried out using thematic analysis to identify patterns of faith interpretation, digital engagement, and ethical practice. The findings indicate that OMK understand evangelization primarily as authentic Christian witness embodied in daily digital interaction rather than merely verbal proclamation. Digital media is perceived not only as a communication tool but as a cultural and pastoral space where faith, identity, and relationships are negotiated. Despite challenges such as performative pressure, digital fatigue, and exposure to conflicting values, OMK demonstrate reflective and responsible engagement in cultivating ethical and humanizing online communication. This study contributes to pastoral theology by positioning youths’ digital experiences as a locus of theological reflection and by mapping the relational connection between evangelization, digital practice, and the sanctification of the digital world.